Diagnostic Performance of Combined Contrast-Enhanced Magnetic Resonance Angiography and Phase-Contrast Magnetic Resonance Imaging in Suspected Subclavian Steal Syndrome. Issue 2 (May 2016) - Tsao, Teng-Fu; Cheng, Kai-Lun; Shen, Chao-Yu; Wu, Ming-Chi; Huang, Hsin-Hui; Su, Chun-Hung; Chen, Fong-Lin; Tyan, Yeu-Sheng; Lin, Yung-Chang
Purpose: The study sought to evaluate the efficacy of magnetic resonance imaging (MRI) in patients with suspected subclavian steal syndrome (SSS) using both contrast-enhanced (CE) MR angiography and phase-contrast (PC) MRI. Methods: Fifteen suspected SSSs from 13 patients were evaluated using CE-MR angiography and PC-MRI. Ten patients also received dynamic CE-MR angiography. Results: All MRI examinations were technically successful. By combining CE-MR angiography with PC-MRI, 10 SSSs were diagnosed in 9 patients. The delay enhancement dynamic technique predicted SSS with a sensitivity, specificity, and accuracy of 57.1%, 100%, and 72.7%, respectively. Without the dynamic technique, affected delay-enhanced arteries were poorly visualized and could be mistaken for occluded vessels. Retrograde vertebral flow by PC-MRI was used to predict ipsilateral SSS with a sensitivity, specificity, and accuracy of 100%, 60%, and 86.7%, respectively. There were 2 false positives including 1 patient with a proximal total occlusion of the affected vertebral artery and another with brachiocephalic steal syndrome rather than SSS. This suggested that retrograde vertebral flow does not always indicate SSS. Conclusions: CE-MR angiography combined with PC-MRI is efficacious when evaluating SSS in clinical practice.